Randomized controlled trial of motion-assisted exposure therapy for posttraumatic stress disorder after mild traumatic brain injury, with and without an eye movement task - Roy, Michael J.; Bellini, Paula; Kruger, Sarah E.; Dunbar, Kerri; Atallah, Hannah; Haight, Thaddeus; Vermetten, Eric (Frontiers in Virtual Reality, 2022)
Background and Purpose: PTSD and mTBI are persistent and frequently comorbid after combat, yet current therapies often achieve only modest impact. A novel exposure-based “walk and talk” cognitive therapy, Motion-Assisted, Multi-Modal Memory Desensitization and Reconsolidation (3MDR), featuring participant-selected music and pictures and an eye movement (EM) task in an immersive virtual environment, has shown efficacy in treatment-resistant male veterans, but has not been studied in women or after TBI. The EM task is adapted from eye movement desensitization and reprocessing (EMDR) therapy, but dismantling studies of EMDR have questioned EM benefit. This pilot study assesses 3MDR in male and female veterans with comorbid PTSD and mTBI, and the impact of EM on response. We hypothesized that 3MDR would prove efficacious, both with (EM+) and without EM (EM-). Design: Participants with probable PTSD (PCL-5 ≥ 34) and mTBI were randomized to EM + or EM-across 10 sessions. Participants provided songs and pictures that they rated on impactfulness. While walking in the 3MDR virtual environment, participants started with a song to bring them back to the time of their trauma, and then traversed two hallways, actively walking toward emotionally evocative pictures that they then discussed with their therapist. Key words or feelings they expressed were superimposed over the picture, then read aloud, whereupon EM + participants recited numbers flashing on a ball crisscrossing the picture. These procedures were repeated for multiple pictures per session. A song to return the participant to present day closed each session. Change in PCL-5 score from pre-to post-intervention was the primary outcome, with additional measures at 3 and 6 months. Results: Sixteen (80%) of 20 participants completed the intervention (8 EM+, 8 EM-); 9 (6 EM+, 3 EM-) had resolution of PTSD diagnosis and two improved significantly without resolution. Average PCL-5 score declined from 52.0 (95% confidence intervals: 46.3, 57.7) at baseline to 33.6 (24.3, 42.9) post-intervention (p < 0.01). The EM + group achieved statistically significant improvement (p = 0.01) while the EM-did not (p = 0.10). Conclusion: For veterans with PTSD and comorbid mTBI, 3MDR is effective, and the EM component may add value. Confirmation with larger studies is important.